Oxidation and reduction of redox-sensitive elements in the presence of humic substances in subsurface environments: A review. (April 2019) - Lee, Seyong; Roh, Younghee; Koh, Dong-Chan
Abstract: The oxidation and reduction (redox) processes of redox-sensitive elements (RSE) in the presence of humic substances (HS) have become a significantly important issue in the terms of biogeochemical cycles. Redox processes are crucial for determining the speciation, mobility, toxicity, and bioavailability of RSE in natural environments. It is known that HS act as an effective redox mediator for accepting and donating electrons, and thereby transfers them to RSE. We review the recent progress in the field of the redox processes of RSE including As, Cr, Cu, Fe, Hg, and Se in the presence of HS. The extent and rate of the redox processes of these RSE are significantly affected by the concentration of functional groups and the chemical composition of HS. In subsurface environments, pH, ionic strength, and the presence of competitive components, microorganisms, and oxygen need to be considered to elucidate the redox processes of RSE in the presence of HS. In addition, improved analytical techniques for the characterization of HS has the potential to advance the study on the redox processes of RSE in the presence of HS. It may contribute to understanding the mechanism for the redox processes between RSE and HS in the biogeochemical cycles. Graphical abstract: Image 1011 Highlights: HS acts as an effective redox mediator via binding and electron transfer to RSE. The redox processes of RSE are influenced by a variety of functional groups in HS. The redox processes of RSE in the presence of HS tend to be pH-dependent reactions.